Current trends and challenges in point-of-care urinalysis of biomarkers in trace amounts - Yeasmin, Sanjida (2023)
Urinalysis enables non-invasive point-of-care (POC) testing of numerous biomarkers at their physiological and elevated levels, obviating the need for sophisticated equipment or trained personnel. POC urinalysis is used to identify biomarkers that are rich in urine (greater than 1 μM), such as lactate, uric acid, glucose, ions, and adenosine. Urine also contains biomarkers such as small molecules, nucleic acids, neurotransmitters, and drugs in trace amounts (less than 1 μM). These biomarkers are of significant importance for health care monitoring, diagnosis of various disorders (cancer, metabolic diseases, etc.) and illicit drug control (cocaine, steroids, etc.). While POC detection of urinary biomarkers at higher concentration (μM to mM) levels is feasible, direct assaying of biomarkers in nM to fM levels is challenging, as assay responses are typically masked by interferences from the urine sample matrix. This report is a consolidated review of emerging trends and challenges in the POC urinalysis for detecting biomarkers that are less abundant in urine. The sensing mechanisms, analytical device fabrication, discrete and integrated sample pre-treatment procedures for POC assaying of urinary markers in trace amounts are elaborated. Subsequently, the utilization of smart data analytics for facilitating personalized urinalysis is presented. A comprehensive outlook on associated challenges in POC urinalysis of biomarkers in trace amounts is further provided, which would facilitate the advancement of POC urinalysis for a wide range of healthcare applications.